2011
DOI: 10.3928/00220124-20111003-04
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Learning Needs of South Carolina Nurses by Exploring Their Perceived Knowledge of Emergency Preparedness: Evaluation of a Tool

Abstract: By prioritizing learning needs based on a needs assessment and accommodating learning preferences, a systematic and planned approach to educating nurses about this extremely important topic can be implemented to significantly strengthen nurses' ability to respond to disaster events competently and effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 48 publications
1
27
1
Order By: Relevance
“…Moreover, the beta regression coefficient demonstrated that each of the seven dimensions had a significant effect on explaining overall emergency preparedness (P < 0.01). Overall, factor analysis, reliability analysis, and regression results support that the revised EPIQ is a reliable and valid instrument (McKibbin et al, 2011).…”
Section: Conceptual Frameworkmentioning
confidence: 75%
See 4 more Smart Citations
“…Moreover, the beta regression coefficient demonstrated that each of the seven dimensions had a significant effect on explaining overall emergency preparedness (P < 0.01). Overall, factor analysis, reliability analysis, and regression results support that the revised EPIQ is a reliable and valid instrument (McKibbin et al, 2011).…”
Section: Conceptual Frameworkmentioning
confidence: 75%
“…First developed by Wisniewski et al (2004), the threepart EPIQ survey is a result of the collaborative efforts of the Wisconsin Nurses Association, Wisconsin Division of Public Health, and Wisconsin Nursing Coalition, to advance emergency preparedness research and assess the training needs of registered nurses to respond to disaster situations (Garbutt et al, 2008;McKibbin et al, 2011;Wisniewski et al, 2004). Today, the EPIQ is the primary instrument used in scientific research to comprehensively assess nurses' perceived knowledge of emergency preparedness (Baack & Alfred, 2013;McKibbin et al, 2011).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 3 more Smart Citations